(untitled) (Hekima Review, 2020)
Liturgy is one of the means by which human beings communicate with God. However, liturgies and liturgical practices emerge on account of the ingenuity of human beings to create and maintain ways through which genuine worship is offered to God. John Searle makes us understand that any social reality created through Collective Intentionality, Assignment of Functions and Constitutive Rules can be considered as an institution. Hence, every institution is created using the formula X is considered as a Y in a C (X=Y in a C). This article is aimed at analyzing how liturgies are created and maintained using the aforesaid formula. Language also plays a key role in the construction of liturgies. It is constitutive of liturgy and without language no liturgy can exist